A Multi-Wave Assessment of Information Security Awareness in Personal Device Use among Brazilian Users - Souza, Arthur C.; Bento, Lucila M. S. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais do XXVI Simpósio Brasileiro de CibersegurançaDO - 10.5753/sbseg.2026.29309, 2026)
Information Security Awareness (ISA) instruments for Brazilian users are scarce, multi-wave evidence remains scarce, and the Knowledge–Attitude–Behavior (KAB) model has been validated mainly in corporate settings. We propose a self-assessment instrument applied across three waves (n = 173). The composite ISA score remained stable (∼65/100), but platformautomated behaviors (OS updates, MFA) improved while agency-dependent behaviors (password rotation, non-reuse, reporting) stagnated. Path analysis showed a dominant direct knowledge–behavior effect (β = 0.46), with attitudinal mediation explaining only 14.5%, contrasting with prior corporate findings. Self-declared concern declined despite intensified cyber-fraud reporting, plausibly reflecting security fatigue. Awareness campaigns should prioritize actionable knowledge over appeals to concern.